Kyrgyz Republic : Enhanced Initiative for Heavily Indebted Poor Countries; Preliminary Document. (IMF Staff Country Reports; Country Report ;, 2006)
This paper presents a preliminary assessment of the Kyrgyz Republic's eligibility for assistance under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. It provides background information on the country's eligibility under the enhanced HIPC Initiative. It summarizes the structure and performance of the economy as well as the poverty profile; analyzes the governance environment; and examines the policy track record and the unfinished reform agenda. This study discusses medium- to long-term macroeconomic projections and outlines the proposed timeline for preparation of the decision point document.